Music from the Wrong Place: On the Italianicity of Quebec Disco - Straw, Will (Criticism, 2018)
One of my favorite compilation CDs of the last few years is Unclassics: Obscure Electronic Funk and Disco, 1975–1985, released in 2004 on the Environ label. The thirteen tracks on Unclassics were collected and remixed by house/techno artist Morgan Geist, who offers them as all-but-forgotten dance music gems from just outside an Anglo-American musical axis, from places like Spain and Italy. The style that ostensibly unites these tracks is “Eurodisco,” though, as we shall see, that label does not accurately subsume all of them. “Italo-disco” seems an even cruder reduction, but circulates among critics, fans, and collectors as a meaningful label for much of the music gathered here. While some of the cuts on Unclassics have long been the idiosyncratic favorites of DJs or dance music collectors, more is going on here than the resurrection of cultish or neglected treasures. Unclassics is one milestone within the significant rehabilitation of European and Italian disco that has unfolded over the last decade. Mixed Up in the Hague, Vol. 1, a compilation first released privately in 1999, was a key event in this rehabilitation; other collections, like I-Robots: Italo Electro Disco Underground Classics and Confuzed Disco: A Retrospective of Italian Records, have followed. Zyx, the Germany-based label that dominated the field in the 1980s and early 1990s, is actively marketing dozens of compilations of its own Italo-disco from that period. The garish red and green covers of Zyx’s Italo anthologies, which filled the discount cassette bins of European airport stores fifteen years ago, have been redesigned so that they now look authoritative and curatorial. Radio and DJ sets devoted to this music now abound on the Internet. Think Italy. Without claiming mind-reading powers, it’s a comfortable prediction you’ve already got tacky piano sample records and frenzied all-night clubbing in mind, a nation that when it isn’t knocking out club records by the cartload likes nothing more than to party all night on a hillside by the sea. Italian music has been in and out of style more often than the flares revival. There are enough piew-piew-piew zaps during these 55 minutes to wipe out a small nation of roller skaters. For almost two decades, tracks like those collected on Unclassics held the status of morbid symptoms, reminders of the decay and dispersion of dance music in the years between disco and house music. Even as they reclaim these tracks as lost gems, the liner notes to Unclassics embrace that morbidity, relishing the ways in which so many of these pieces are seen to have gotten things wrong. My favorite track on Unclassics is a Spanish cut from 1979, “Margherita,” whose guiltless dishing out of pleasures betrays the compilation’s broader sensibility. Piercing little synth notes alternate with thick, rolling movements that could drive an army forward. Mariachi horns interweave with tinny keyboard glissandos in rounding out sections. Changes come precisely when we want them; each gimmicky sound or flourish dutifully returns just as we start to miss it. As “Margherita” moves in unstoppable fashion around its wheel of styles and sections, it is easy to think that this is music trying too desperately to be liked. Dominant understandings of the European contribution to disco read its influence selectively, focusing on the robotic, synthesized sounds of Kraftwerk or Giorgio Moroder. These versions of Eurodisco’s history link such figures as Can, Patrick Cowley, Afrika Bambaataa, and Juan Atkins in a heroic story that sends disco to Europe so that it may return, reinvented, to an American underground able to realize its radical potential. When Eurodisco is remembered for its sleek mechanical control, however, what gets forgotten is the lush extravagance that seemed to mark so much of it. As early as 1977, North American critics had recourse to a well-entrenched moral geography in characterizing disco music from continental Europe as “florid,” given to flamboyant passion and bombastic overlays of effects.1 Arguably, the peculiarity of so much Eurodisco came from the ways in which its extravagant lushness often went hand in hand...